Tinkering with executive term limits: partisan imbalances and institutional legacies in Latin America. Issue 1 (2nd January 2022) - Negretto, Gabriel L.
ABSTRACT: Why are some democratically elected presidents more likely than others to extend or remove their current term limits? This paper argues that the frequency and type of reforms relaxing executive term limits depend on the relative partisan power of presidents and on inherited institutional constraints. These reforms are more likely when short-term shifts in the distribution of partisan resources significantly favour an incumbent executive vis-à-vis the opposition. Yet partisan imbalances do not fully account for the observed variation in outcomes across presidential democracies. Long-standing institutional legacies also affect whether presidents are willing and able to ease existing term limits. Specifically, the maintenance of effective executive constraints over time reduces the probability that incumbents facing restrictions on consecutive re-election will obtain a one-term extension and makes it extremely unlikely that they will abolish term limits altogether. A statistical analysis of reforms allowing consecutive executive re-election in Latin America between 1978 and 2015 and a comparison between Ecuador and Colombia support these arguments.